The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/s0034-71082000000200002
|View full text |Cite
|
Sign up to set email alerts
|

Competição larval em Chrysomya megacephala (F.) (Diptera: Calliphoridae): efeitos de diferentes níveis de agregação larval sobre estimativas de peso, fecundidade e investimento reprodutivo

Abstract: Larval competition in Chrysomya megacephala (F.) (Diptera: Calliphoridae): effects of different levels of larval aggregation on estimates of weight, fecundity and reproductive investmentIn insects that utilize patchy and ephemeral resources for feeding and egg laying, the outcome of larval competition for food resources depends on the amount of resources and the spatial distribution of immatures among patches of food. In the present study, the results of larval competition for food in Chrysomya megacephala, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
0
15
0
3
Order By: Relevance
“…The larval viability rate in the gizzard homogenate diet was 73% (60 g of diet for 40 larvae = 1.5 g of diet per larva), presenting a similar rate to that reported by Godoy et al (1996), who used an artificial diet, and the rate reported by Leal et al (1982), of 73.25% at a density of 50 g of diet for 100 larvae (0.5 g of diet per larva) and at the 20 other densities tested with smaller quantities of diets fed to larvae. The diet used by Leal et al (1982) has been used by several other authors (Von Zuben et al 2000; Estrada et al 2009), and the achievement of a similar viability indicates a good result.…”
Section: Discussionmentioning
confidence: 92%
“…The larval viability rate in the gizzard homogenate diet was 73% (60 g of diet for 40 larvae = 1.5 g of diet per larva), presenting a similar rate to that reported by Godoy et al (1996), who used an artificial diet, and the rate reported by Leal et al (1982), of 73.25% at a density of 50 g of diet for 100 larvae (0.5 g of diet per larva) and at the 20 other densities tested with smaller quantities of diets fed to larvae. The diet used by Leal et al (1982) has been used by several other authors (Von Zuben et al 2000; Estrada et al 2009), and the achievement of a similar viability indicates a good result.…”
Section: Discussionmentioning
confidence: 92%
“…Interspecific interactions in blowfly system have been investigated in experiments in which population dynamics and competitive ability of the invading species C. rufiffacies and C. albiceps, and of the native species C. macellaria were analyzed (Wells & Greenberg 1992a,b,c, 1994, Wells & Kurahashi 1997, Faria et al 1999, Reis et al 1999, Von Zuben et al 2000. These investigations were attempts to gain a deeper understanding of recent blowfly biological invasion in Americas and its implications on population dynamics.…”
mentioning
confidence: 99%
“…On the other hand, high levels of larval aggregation may cause unfavorable conditions for the maggots (Rivers et al 2011) such as negative influence on adult female fertility and reproductive investment, maggot size on final stages of development, and weight of the resulting adults (Kamal 1958, Levot et al 1979, Von Zuben et al 2000, Ireland & Turner 2006, Reigada & Godoy 2006. Goodbrod & Goff (1990) showed that the optimal larval density for C. megacephala is 8 larvae/g of the substrate.…”
Section: Discussionmentioning
confidence: 99%